The battle for Congress : consultants, candidates, and voters - Thurber, James A., 1943- (Brookings Institution Press, 2001)
This volume provides an in-depth examination of six political campaigns waged during competitive 1998 races for the U.S. House of Representatives. The case studies evaluate the professional political consultants who managed each campaign, their interaction with the candidates, and the impact of the campaigns on voters. Relying on unparalleled access to both the consultants involved and the candidates themselves, the contributors explore the electoral setting and context of the congressional districts, the strategy, theme, and message of each campaign, the consultants' decisionmaking, fund-raising, and spending, and any outside forces that entered into the races. The book features new data on tracking, polls, and television advertising budgets.